LncRNA FOXD2-AS1 Increased Proliferation and Invasion of Lung Adenocarcinoma via Cell-Cycle Regulation - Yuan Y; Yu P; Shen H; Xing G; Li W (Dove Medical Press, 2023)
Yuan Yuan, Peng Yu, Huihua Shen, Guozhu Xing, Wu Li Department of Cardiothoracic Surgery, Xinjiang Military Region General Hospital, Urumqi, People's Republic of ChinaCorrespondence: Yuan Yuan; Wu Li, Department of Cardiothoracic Surgery, Xinjiang Military Region General Hospital, No. 359, Youhao North Road, Urumqi, 830000, Xinjiang, People's Republic of China, Tel +86-13899886276 ; +86-991-4992101, Email doctor_yyuan@163.com; doctorli_xxwk@163.comBackground: Long non-coding RNA FOXD2 antisense RNA 1 (FOXD2-AS1) has been reported in many malignancies. However, the molecular mechanism of many actions is not clarified. This study was conducted to investigate the function of FOXD2-AS1 in lung adenocarcinoma and its molecular mechanism.Methods: Bioinformatics and in vitro analysis including RT-qPCR, CFU, CCK8, Transwell, Cell Apoptosis and Cell Cycle Assay were used for the analysis of gene expression and related effects.Results: It revealed increased expression of lncRNA FOXD2-AS1 in lung adenocarcinoma cell lines (A549 cells), and abundant expression of lncRNA FOXD2-AS1 was also observed in the acquired lung adenocarcinoma tissues. In vitro results showed that knockdown of lncRNA FOXD2-AS1 in A549 cells weakened cell proliferation, invasion and increased apoptosis. At the same time, we found that reducing the expression of lncRNA FOXD2-AS1 caused cell cycle arrest in the G1/S phase. Differential gene analysis of lung adenocarcinoma and adjacent normal tissues showed that the cell cycle and its related process regulation were significantly enriched. Gene Set Enrichment Analysis (GSEA) analysis showed that miR-206, miR-143, lL6-JAK-STAT3 signalling pathway, STAT3, E2F targets, EZH2, P53 signalling pathway and E2F3 targets interacting with lncRNA FOXD2-AS1 were also enriched.Conclusion: This study demonstrates the role and mechanism of the lncRNA FOXD2-AS1 in lung adenocarcinoma and provides a better understanding for the treatment of lung adenocarcinoma, which indicates that interfering with lncRNA FOXD2-AS1 expression may be a novel strategy.Keywords: lncRNA FOXD2-AS1, lung adenocarcinoma, non-small cell lung cancer, cell cycle, proliferation